2021
DOI: 10.1021/acs.nanolett.1c02777
|View full text |Cite
|
Sign up to set email alerts
|

Broadband GaAsSb Nanowire Array Photodetectors for Filter-Free Multispectral Imaging

Abstract: Highly compact, filter-free multispectral photodetectors have important applications in biological imaging, face recognition, and remote sensing. In this work, we demonstrate room-temperature wavelength-selective multipixel photodetectors based on GaAs 0.94 Sb 0.06 nanowire arrays grown by metalorganic vapor phase epitaxy, providing more than 10 light detection channels covering both visible and near-infrared ranges without using any optical filters. The nanowire array geometry-related tunable spectral photore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…In addition, it can be observed from both simulated and measured absorption spectrum that the absorption is red-shifted as the w increases with a fixed period, that means the absorber is a strong width-dependent absorption. This is due to the strong resonant modes supported in the different width of the strip would efficiently couple the incident light at different wavelengths [36]. The wavelength selectivity of this absorber is beneficial to our design of different target wavelengths, which is crucial for practical applications.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it can be observed from both simulated and measured absorption spectrum that the absorption is red-shifted as the w increases with a fixed period, that means the absorber is a strong width-dependent absorption. This is due to the strong resonant modes supported in the different width of the strip would efficiently couple the incident light at different wavelengths [36]. The wavelength selectivity of this absorber is beneficial to our design of different target wavelengths, which is crucial for practical applications.…”
Section: Methodsmentioning
confidence: 99%
“…Miniaturized spectrometers with advantages of portability and low cost and power consumption have attracted much attention due to their potential in advanced application scenarios, including wearable devices, hyperspectral imaging, and internet of things. Computational spectrum reconstruction based on a series of response-modulated photodetectors with a gradient bandgap is one of the most promising methods for achieving such miniaturized spectroscopy systems. For instance, Yang et al successfully demonstrate a miniaturized spectrometer at the scale of tens of micrometers using a single compositionally graded CdS x Se 1– x nanowire . Recently, halide perovskites have also been used in photodetectors for human visual-like spectrum projection, full-color detection, and multispectral recognition owing to their outstanding properties such as facile solution-process fabrication, excellent light harvesting coefficients, and tunable bandgaps. Xu et al demonstrated a miniaturized multispectral detector based on a composition-gradient perovskite microwire detector array, offering a response edge ranging from 450 to 790 nm .…”
Section: Introductionmentioning
confidence: 99%
“…This article provides a new perspective for exploration of new materials and strategies for the development of next generation high performance imaging camera technology. By adopting this approach, with complementary material systems and novel structures, such as III-V semiconductors 10 , 2-D materials 11 , and metasurfaces 12 , we are a step closer to mimicking of the sophisticated biological eyes that are not only sensitive to the visible light, but also to the infrared, and THz wavelengths, with associated polarization and phase information.…”
mentioning
confidence: 99%